0404 Patient and Provider Preferences for Oxybate Treatment for Narcolepsy: A Discrete Choice Experiment. (25th May 2022) - Morse, Anne Marie; Krahn, Lois; Kushida, Clete; Thorpy, Michael; Flygare, Julie; Seiden, David; Athavale, Amod; Gudeman, Jennifer
Abstract: Introduction: Currently available immediate-release sodium oxybate (SXB) and mixed-salt oxybates are dosed twice nightly (second 2.5–4 hours after first). Extended-release, once-nightly SXB (ON-SXB; FT218) is in development. To characterize drivers of oxybate treatment attribute preferences, discrete choice experiments (DCEs) were conducted for both patients and healthcare providers (HCPs). Methods: Thirty-minute web-based surveys were fielded to 1) adults with self-reported physician-diagnosed narcolepsy with/without prior/current use of oxybate, and 2) board-certified/board-eligible HCPs treating ≥5 narcolepsy patients in the last month. Choice sets of 2 hypothetical treatment profiles were generated combining attributes of twice-nightly SXB, mixed-salts oxybate, and ON-SXB. While viewing 12 choice sets, each participant indicated (1) their preferred product overall, (2) the product that would improve quality of life (QoL), and (3) the product that would result in less patient stress/anxiety. Results were analyzed using a mixed logit model. Results: For patients (n=120) and HCPs (n=100), the most important attribute driving overall product choice was dosing frequency (relative attribute importance, 26.0 and 46.1, respectively), with once-nightly preferred over twice-nightly dosing (relative preference weight, ±25.6 and ±43.6); QoL (relative attribute importance, 28.7 and 41.7), with once-nightly preferred over twice-nightly dosing (relative preference weight, ±25.7 and ±38.5); and reducing patient anxiety/stress (relative attribute importance, 26.7 and 44.0), with once-nightly preferred over twice-nightly dosing (relative preference weight, ±23.9 and ±41.6). Other drivers of overall product choice were as follows: patients, clinical efficacy and sodium content (relative attribute importance, 23.5 and 20.8); HCPs, adverse reactions and sodium content (relative attribute importance, 19.7 and 18.6). Drivers of QoL preference were as follows: patients, clinical efficacy and sodium content (relative attribute importance, 28.3 and 20.9); HCPs, adverse reactions and clinical efficacy (relative attribute importance, 21.5 and 18.6). Drivers of reducing patient anxiety/stress were as follows: patients, clinical efficacy and sodium content (relative attribute importance, 17.4 and 17.3); HCPs, adverse reactions and sodium content (relative attribute importance, 18.2 and 14.2). Conclusion: Dosing frequency was identified as the most important attribute driving preference for overall product choice, QoL, and reducing patient anxiety/stress for both patients and HCPs with once-nightly preferred over twice-nightly dosing. Support (If Any): Avadel Pharmaceuticals